POLITICAL ASSESSMENT OF QATARI CRISIS ON THE GCC SECURITY - Mohammed Salam Al-Hashami; Sulastry Yurni Ahmad (Universitas Padjadjaran, 2023)
Through investigating the conception of the Gulf Cooperation Council (GCC) member states, it is obvious that the unity is the main factor that ensured the stability and security of the state members. Due to some political concerns, the Kingdom of Saudi Arabia (KSA), United Arab Emirates (UAE) and State of Bahrain launched boycott policies against the State of Qatar. Accordingly, Qatar has increased its alliance with Turkey and Iran to ensure its national security. The focal aims of this thesis are to explore the consequences of the Qatari Crisis on social, economic, political and mainly on the security sides. Moreover, identifying the key sources of friction between Qatar and the blockading states and how other factors, both historical and contextual have contribute and shaped these differences to the point that the states were willing to engage in such dramatic moves against each other. To achieve these objectives, the study applied qualitative method. A semi-structured questionnaire was used to conduct elite interviews. A semi-structured interview was developed by the researcher for collecting the required data. The interviews focused on the three main political levels which are the strategic, supervisory and executive level. The research provides important solutions for the states in the Gulf region and how to go about their diplomatic and political maneuvers given the significant risks that may be involved. This research used the Theory of Alliance to explore the attitude of the gulf countries along with the situations held on the blockade. The findings revealed that the root causes of the Qatari Crisis are multi-dimensional and include historical, political, economic factors and the media.